Unmet contraceptive needs in rural communities in the Dominican Republic during an international Zika virus outbreak. Issue 3 (4th August 2017) - Shaw, Rebecca; Simmons, Michaela; Nelson, Corrine; Bachelor, Brooke; Adamian, Shant; Frausto, Ana
Abstract : Women living in rural Dominican communities are aware of Zika virus, but education about the virus and access to long‐term reversible contraception are needed.